Ground thermal regimes in Western Dronning Maud Land, Antarctica in 2016 - Masebe, Consliah Tebogo (Rhodes University, Faculty of Science, Department of Geography, 2019)
Research shows that the climate of Antarctica is changing and, it is vital that the change is monitored to understand how it will affect global ecosystems. Since the International Polar Year (IPY) 2007-2008, research in permafrost studies has grown. However, there are still existing gaps that impede complete understanding of Antarctic cold environments and landscape processes. Permafrost has been noted as one of the major controlling factors of the terrestrial ecosystem dynamics in Antarctica. However, the understanding of Antarctic permafrost, when compared to other cryospheric components, is limited, especially its thermal and physical properties, evolution, as well as links to pedogenesis, hydrology, geomorphic dynamics, and responses to global change. This project provided an understanding and insight to over-arching research that evaluates the state and status of permafrost and the active layer in Dronning Maud Land (DML) through examining short-term variations on ground thermal regimes. The main focus is on understanding the influence of synoptic, diurnal and seasonal events on the active layer in 2016. Analysis of available data shows that ground thermal regimes are influenced by variations in air temperature, pressure, wind speed and to some extent, relative humidity. Subsequently, ground thermal regimes also depend on soil physical characteristics including sediment particle size and bulk density. Furthermore, sediment particle size and bulk density have been found to have a great influence on thermal propagation rates as well as active layer depth; the higher the bulk density, the higher the thermal propagation rate and the lower the bulk density, the lower the thermal propagation rate. Conversely, a large proportion of bigger sediment particle size in soil corresponds with a higher thermal propagation rate and a large proportion of smaller sediment particle size in soil corresponds with a lower thermal propagation rate. Also, ground thermal regimes vary according to seasons. Ground temperatures are more variable in summer, while air temperatures are more variable in winter. The variability according to different seasons shows that the active layer responds to seasonal climatic variations. Additionally, the active layer also responds to synoptic and diurnal weather events.
Keywords: Climatic changes -- Antarctica; Frozen ground -- Research -- Antarctica; Frozen ground -- Thermal properties -- Antarctica; Queen Maud Land; Earth temperature -- Antarctica; Soil temperature -- Antarctica -- Measurement